2014
DOI: 10.1051/0004-6361/201322516
|View full text |Cite
|
Sign up to set email alerts
|

The 100-monthSwiftcatalogue of supergiant fast X-ray transients

Abstract: Context. Supergiant fast X-ray transients (SFXTs) are high mass X-ray binaries (HMXBs) that are defined by their hard X-ray flaring behaviour. During these flares they reach peak luminosities of 10 36 -10 37 erg s −1 for a few hours (in the hard X-ray), which are much shorter timescales than those characterizing Be/X-ray binaries. Aims. We investigate the characteristics of bright flares (detections in excess of 5σ) for a sample of SFXTs and their relation to the orbital phase. Methods. We have retrieved all S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 91 publications
(130 reference statements)
5
61
0
Order By: Relevance
“…The outbursts of these sources last for a few hours at the most, and thus their activity duty cycle is estimated to be typically of a few percent (Lutovinov et al 2013;Romano et al 2011Romano et al , 2014aBozzo et al 2015). In virtually all SFXTs it has also been observed that X-ray flares reaching a luminosity of 1−10% of that of the brightest outbursts can occur at any time, displaying timing and spectral properties similar to those of the more luminous events (see, e.g., Sidoli et al 2008;Bozzo et al 2010;Bodaghee et al 2010;Romano et al 2013Romano et al , 2014b.…”
Section: Introductionmentioning
confidence: 99%
“…The outbursts of these sources last for a few hours at the most, and thus their activity duty cycle is estimated to be typically of a few percent (Lutovinov et al 2013;Romano et al 2011Romano et al , 2014aBozzo et al 2015). In virtually all SFXTs it has also been observed that X-ray flares reaching a luminosity of 1−10% of that of the brightest outbursts can occur at any time, displaying timing and spectral properties similar to those of the more luminous events (see, e.g., Sidoli et al 2008;Bozzo et al 2010;Bodaghee et al 2010;Romano et al 2013Romano et al , 2014b.…”
Section: Introductionmentioning
confidence: 99%
“…Supergiant fast X-ray transients (SFXTs) are high mass X-ray binaries (HMXBs) hosting a neutron star (NS) and an OB supergiant companion (Sguera et al 2005;Negueruela et al 2006) which display X-ray flares reaching, for a few hours, 10 36 −10 37 erg s −1 (see Romano et al 2014c, for a recent review). This is at odds with normal supergiant HMXBs, which display a fairly constant average luminosity with typical variations of a factor of 10−50 on time scales of a few hundred to thousands of seconds; SFXTs are also significantly subluminous with respect to classical Sg-HMXBs like Vela X-1 (Bozzo et al 2015), and show a dynamical range up to 5 orders of magnitude, as their luminosities can be as low as ∼10 32 erg s −1 during quiescence (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been showing large flux swings since its discovery (in 't Zand et al 2004;in 't Zand 2005;Rampy et al 2009;Romano et al 2014c), with the brightest flux recorded by Swift/XRT (Burrows et al 2005) during the 2013 June 28 outburst (Romano et al 2013a) at ∼6.5 × 10 −9 erg cm −2 s −1 (0.3−10 keV, unabsorbed) Tables 1 and 2, and Fig. 2 are available in electronic form at http://www.aanda.org corresponding to L ∼ 10 37 erg s −1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They show high dynamic ranges (between 100 and 10,000, depending on the specific source; e.g. [46,47]) and their X-ray spectra in outburst are very similar to accreting pulsars in HMXBs. In fact, half of them have measured neutron star (NS) spin periods similar to those observed from persistent HMXBs (see [48] for a recent review).…”
Section: Sfxtsmentioning
confidence: 99%